Widely Assumed but Thinly Tested: Do Employee Volunteers' Self-Reported Skill Improvements Reflect the Nature of Their Volunteering Experiences? - Jones, David A. (Frontiers in Psychology, 2016)
An increasing number of companies use corporate volunteering programs (CVPs) to support and coordinate their employees' efforts to serve their communities. Among the most frequently touted benefits of such programs to sponsoring companies and employee volunteers alike is the opportunities for employees to develop tangible work-related skills through their volunteering activities. Evidence for skill development through volunteering, however, is mostly limited to the expressed beliefs of corporate leaders and employee volunteers. This study was designed to contribute to this largely anecdotal literature by testing hypotheses about the extent to which employee volunteers' self-reported skill development reflects the characteristics of the volunteers and their volunteering experiences. Study participants were 74 employee volunteers who completed a service apprenticeship managed by a U.S.-based nonprofit called Citizen Schools that partners with middle schools to extend the learning day with a combination of academic support, enrichment, and youth development activities. Data were obtained via the nonprofit's records, and surveys completed by employee volunteers before and after their service experience, including measures used to assess self-reported improvements in each of 10 work-related skills: communicating performance expectations, leadership, mentorship, motivating others, project management, providing performance feedback, public speaking and presenting, speaking clearly, teamwork, and time management. Support was found for several hypothesized effects suggesting that employees who practiced specific skills more often during their volunteering experience reported greater improvements in those skills. Improvements in some skills were higher among employee volunteers who completed a greater number of pre-volunteering preparation courses, and the effects of preparation courses were moderated by the employee volunteers' self-efficacy about improving their work-related skills on all 10 skills as hypothesized. I discuss the implications of these findings for theory and research, and provide suggestions for designing volunteer experiences that encourage service commitments from companies and their employees, and ultimately create tangible value for them and meaningful social value for their communities.